Chemical composition and antimicrobial activity of the essential oils of Onychopetalum amazonicum R.E.Fr. Issue 20 (17th October 2016) - de Lima, Bruna R.; da Silva, Felipe M. A.; Soares, Elzalina R.; de Almeida, Richardson A.; da Silva Filho, Francinaldo A.; Pereira Junior, Raimundo C.; Hernandez Tasco, Álvaro J.; Salvador, Marcos J.; Koolen, Hector H. F.; de Souza, Afonso D. L.; Pinheiro, Maria L. B.
Abstract: The essential oils from leaves, twigs and trunk bark of Onychopetalum amazonicum R.E. Fr. (Annonaceae), obtained by hydrodistillation, were analysed by GC and GC–MS, and also were evaluated for in vitro antimicrobial activity. Forty-one compounds, which correspond to 75.0–92.2% of the oil components, were identified. Major compounds were sesquiterpenes, including ( E )-caryophyllene, caryophyllene oxide, spathulenol, α-gurjunene, allo -aromadendrene and α- epi -cadinol. The oils were evaluated for antimicrobial activities against four bacteria strains and five pathogenic fungi. The oil of the trunk bark exhibited good activity against Staphylococcus epidermidis ATCC 12228, Escherichia coli ATCC 10538 and Kocuria rhizophila ATCC 9341, with a minimal inhibitory concentration of 62.5 μg/mL. The essential oil composition and the antimicrobial evaluation are reported for the first time for the genus Onychopetalum . Abstract :